Balancing Efficiency and Spirituality: Implementation of Virtual Accounts at Tebuireng Islamic Boarding School - Humaidi Humaidi; Dwi Ari Pertiwi; Rachma Agustina; Meta Ardiana; Srikalimah (Universitas Islam Negeri Ar-Raniry, 2026)
The rapid expansion of financial digitalization has transformed governance practices in educational institutions, including Islamic boarding schools (pesantren), where financial transactions are closely intertwined with social and spiritual values. This study aims to examine how the implementation of virtual account (VA) systems at Tebuireng Islamic Boarding School influences administrative efficiency, user satisfaction, and socio-spiritual dynamics. This study employs a qualitative approach with an interpretive phenomenological design. Data were collected through in-depth interviews, participatory observations, and document analysis involving fifteen participants, including financial staff, students’ guardians, and institutional managers. The findings indicate that the adoption of VA significantly enhances administrative efficiency through real-time transaction processing, improved transparency, and reduced recording errors, reflecting the principles of New Public Management (NPM). From the perspective of the Technology Acceptance Model (TAM), perceived usefulness and ease of use contribute to increased satisfaction; however, trust and alignment with spiritual values emerge as equally important determinants. Using Cultural-Historical Activity Theory (CHAT), the study further reveals that digitalization reconfigures social interactions, reducing face-to-face engagement traditionally associated with silaturahmi and barakah, thereby generating tensions between efficiency and spirituality. This study contributes to the literature by demonstrating that financial digitalization in religious institutions is a value-laden process that requires balancing technological efficiency, user trust, and spiritual meaning, offering implications for the development of hybrid governance models in faith-based educational settings. ABSTRAK - Menyeimbangkan Efisiensi dan Spiritualitas: Implementasi Virtual Account di Pesantren Tebuireng. Perkembangan digitalisasi keuangan telah membawa perubahan signifikan dalam tata kelola lembaga pendidikan, termasuk pesantren, yang praktik keuangannya tidak terlepas dari nilai sosial dan spiritual. Penelitian ini bertujuan untuk menganalisis bagaimana implementasi sistem virtual account (VA) di Pondok Pesantren Tebuireng memengaruhi efisiensi administrasi, kepuasan wali santri, serta dinamika sosial-spiritual yang menyertainya. Penelitian ini menggunakan pendekatan kualitatif dengan strategi fenomenologi interpretatif, melalui wawancara mendalam, observasi partisipatif, dan studi dokumen terhadap lima belas informan yang terdiri dari staf keuangan, wali santri, dan pengelola pesantren. Hasil penelitian menunjukkan bahwa penggunaan VA mampu meningkatkan efisiensi administrasi secara signifikan melalui pencatatan transaksi secara real-time, peningkatan transparansi, dan pengurangan kesalahan pencatatan, sejalan dengan prinsip New Public Management (NPM). Dari perspektif Technology Acceptance Model (TAM), kemudahan dan kegunaan sistem meningkatkan kepuasan pengguna, namun faktor kepercayaan serta kesesuaian dengan nilai spiritual juga menjadi penentu utama. Sementara itu, melalui pendekatan Cultural-Historical Activity Theory (CHAT), ditemukan bahwa digitalisasi mengubah pola interaksi sosial dengan berkurangnya kontak langsung yang sebelumnya mengandung nilai silaturahmi dan keberkahan, sehingga memunculkan ketegangan antara efisiensi dan spiritualitas. Penelitian ini menegaskan bahwa digitalisasi keuangan di pesantren merupakan proses yang sarat nilai, sehingga memerlukan keseimbangan antara efisiensi teknologi, kepercayaan pengguna, dan makna spiritual dalam pengembangan tata kelola yang berkelanjutan.